Initiation of Snowball Earth with volcanic sulfur aerosol emissions. Issue 4 (22nd February 2017) - Macdonald, F. A.; Wordsworth, R.
Abstract: We propose that the first Neoproterozoic Snowball Earth event, the Sturtian glaciation, was initiated by the injection of sulfate aerosols into the stratosphere. Geochronological data indicate that the Natkusiak magmatic assemblage of the Franklin large igneous province coincided with onset of the Sturtian glaciation. The Natkusiak was emplaced into an evaporite basin and entrained significant quantities of sulfur, which would have led to extensive SO2 and H2 S outgassing in hot convective plumes. The largest of these plumes could have penetrated the tropopause, leading to stratospheric sulfate aerosol formation and an albedo increase sufficient to force a Snowball. Radiative forcing was maximized by the equatorial location of the Franklin and the cool Neoproterozoic background climate, which would have lowered the tropopause height, increasing the rate of stratospheric aerosol injection. Our results have implications for understanding Phanerozoic mass extinction events, exoplanet habitability, and aerosol perturbations to the present‐day climate. Key Points: The Franklin large igneous province was coincident with onset of the Sturtian Snowball Earth glaciation Multiyear to decadal fissure eruptions can inject enough sulfur aerosols to the stratosphere to initiate Snowball Earth Cold background climate states are sensitive to ice‐albedo catastrophe because tropopause height is a function of surface temperature